IMPLEMENTASI KEBIJAKAN DAN STRATEGI DAERAH (JAKSTRADA) DALAM PENGELOLAAN SAMPAH DI KABUPATEN DEMAK - Nawangsari, Hasna Ulayya; Rostyaningsih, Dewi; Lestari, Hesti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Demak Regency is one of the regions that is not spared from waste problems. The waste issues in Demak Regency consist of high population growth, lack of community participation, rampant use of single-use plastic in the form of packaged drinks, landfill sites still used for open dumping, limited human resources, limited budget, and limited fleet. Based on these issues, the central government has directed each region to formulate regional policies and strategies as guidelines for the implementation of household waste and similar waste management. This research aims to analyze the implementation of the regional policies and strategies, as well as identify factors that influence the implementation of these regional policies and strategies in waste management in Demak Regency. This research employed a qualitative descriptive method through interviews, observations, and documentation. The results demonstrate that the implementation of the regional policies and strategies in waste management in Demak Regency has not yet achieved the right policy, right implementer, right target, and right process. This is due to ongoing issues such as the increasing use of plastic in the form of packaged drinks, limited human resources, limited budget, limited infrastructure, lack of private sector involvement in waste reduction, and lack of community participation. The recommendation given is that the Environmental Agency needs to re-evaluate the implementation of the regional policies and strategies in waste management, improve work patterns, enhance cooperation between the government and the private sectors in waste reduction, and maximize community empowerment.